Combining a NHS ester and glutaraldehyde improves crosslinking prior to MALDI MS analysis of intact protein complexes. (25th August 2015) - Boeri Erba, Elisabetta; Klein, Pierre Andre; Signor, Luca
Abstract : Protein complexes play pivotal roles in cellular life. Nevertheless, their characterization remains a substantial challenge. Mass spectrometry (MS) is an emerging tool to study protein assemblies, and electrospray ionization (ESI) is often used because it preserves non‐covalent interactions. Matrix‐assisted laser desorption/ionization (MALDI) represents an important alternative to ESI because it is more tolerant to salts and detergents (e.g. necessary in the case of membrane complex analyses). Prior to MALDI‐MS, the subunits should be crosslinked (XLed). Moreover, crosslinking (XLing) is useful when constraint distances are determined to obtain low‐resolution structural information. Here we report a novel XLing approach to study protein complexes with MALDI‐MS. We investigated two tetramers (i.e. alcohol dehydrogenase and aldolase) larger than 140 kDa at two pH values (7.2 and 8.0). We tested two different crosslinkers (XLers) (i.e. BS 3 and glutaraldehyde), used separately or in combination. We utilized gentle agitation and ultracentrifugation. Our data shows that the pH influenced the XLing when using a single XLer. Combining two XLers was demonstrated to be more efficient than using a reagent alone. In particular, the combination determined a higher degree of XLing and lower mass shift. This could suggest a ranking in target amino acid availability. First residues at specific distances are linked by BS 3, then glutaraldehyde binds residues that are still available at larger distances. Ultracentrifugation and gentle agitation both provide similar degrees of XLing, but the former method determined a lower mass increment resulting from redundant XLing. To conclude, we present an efficient dual XLing approach for determining mass and stoichiometry of protein assemblies. Copyright © 2015 John Wiley & Sons, Ltd.